2017
DOI: 10.1111/jav.01294
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of feather microstructure to eider down insulation properties

Abstract: Insulation is an essential component of nest structure that helps provide incubation requirements for birds. Many species of waterfowl breed in high latitudes where rapid heat loss can necessitate a high energetic input from parents and use down feathers to line their nests. Common eider Somateria mollissima nest down has exceptional insulating properties but the microstructural mechanisms behind the feather properties have not been thoroughly examined. Here, we hypothesized that insulating properties of nest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 27 publications
1
31
1
Order By: Relevance
“…The lack of observable differences in contour feathers may be related to strong constraints of the waterproof capability of this important outer plumage layer in a species that forages underwater. Further investigation is warranted to examine the microstructures of these feathers (D’alba et al 2017), quantify insulative capacity of the plumage (Walsberg 1988), and determine if these patterns between habitats are repeated across the latitudinal range of M. armata subspecies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The lack of observable differences in contour feathers may be related to strong constraints of the waterproof capability of this important outer plumage layer in a species that forages underwater. Further investigation is warranted to examine the microstructures of these feathers (D’alba et al 2017), quantify insulative capacity of the plumage (Walsberg 1988), and determine if these patterns between habitats are repeated across the latitudinal range of M. armata subspecies.…”
Section: Resultsmentioning
confidence: 99%
“…Merganetta armata sampled from the high-altitude study area (Figure 2) had longer, denser down plumage in the pectoral tract compared to the low-altitude study area (Figure 3). Research has shown that differences in down microstructure are related to differences in insulative properties, as long fibers increase the air-trapping capacity of the feather (D’alba et al 2017). While our observed differences may appear inconsequential from feather to feather, a difference of 3-4 barbs and 2mm of length in the average down feather across the whole body would be expected to have substantial effects on the overall plumage of the animal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations